Crack Mechanisms and Crack Interaction in Thin Films - Krabbe, Mads (Technical Report Mechanical Engineering, 2012)
The report contains a description of the theory for throughsurface channeling crack in thin film systems. Key topics and mechanisms are described including channeling criteria, crack interaction and elastic mismatch in the system. A case of radial cracks spreading from a Rockwell indenter is used to describe how the theory can be used to determine fracture toughness and residual stresses in a thin film.